SIGNIFICANCE AND PRINCIPLES OF ENVIRONMENTAL TAXATION - L. S. Samodelko; M. V. Karp (Вестник университета, 2020)
Greening of taxation is an actual vector of reforming the tax system in the Russian Federation. However, the principal approaches of this tool for regulating economic processes currently require comments and explanations, as well as justification of the legality of their application. The article considers this issue and identifies methods and  approaches for the practical implementation of the tax mechanism for regulating environmental processes in  the Russian Federation. Based on a comparative analysis of various scientific sources, the authors offer their own vision of the fundamental requirements for environmental taxation and provide their justification. The results of the  research can be used in building the state’s tax policy from the position of environmental regulation and  formation of the conceptual foundations of this mechanism for regulating environmental processes.